Endocrine Society of Australia position statement on male hypogonadism (part 1): assessment and indications for testosterone therapy. Issue 4 (15th August 2016) - Yeap, Bu B; Grossmann, Mathis; McLachlan, Robert I; Handelsman, David J; Wittert, Gary A; Conway, Ann J; Stuckey, Bronwyn GA; Lording, Douglas W; Allan, Carolyn A; Zajac, Jeffrey D; Burger, Henry G
Abstract: Introduction: This article, Part 1 of the Endocrine Society of Australia's position statement on male hypogonadism, focuses on assessment of male hypogonadism, including the indications for testosterone therapy. (Part 2 will deal with treatment and therapeutic considerations.) Main recommendations: Key points and recommendations are: Pathological hypogonadism arises due to diseases of the hypothalamus or pituitary gland (hypogonadotropic hypogonadism) or testes (hypergonadotropic hypogonadism). It is a clinical diagnosis with a pathological basis, confirmed by hormone assays. Hormonal assessment is based on measurement of circulating testosterone, luteinising hormone (LH) and follicle‐stimulating hormone (FSH) concentrations. Measurement of sex hormone‐binding globulin levels can be informative, but use of calculated free testosterone is not recommended for clinical decision making. Testosterone replacement therapy is warranted in men with pathological hypogonadism, regardless of age. Currently, there are limited data from high‐quality randomised controlled trials with clinically meaningful outcomes to justify testosterone treatment in older men, usually with chronic disease, who have low circulating testosterone levels but without hypothalamic, pituitary or testicular disease. Obesity, metabolic syndrome and type 2 diabetes are associated with lowering of circulating testosterone level, but without elevation of LH and FSH levels. Whether these are non‐specific consequences of non‐reproductive disorders or a correctable deficiency state is unknown, but clear evidence for efficacy and safety of testosterone therapy in this setting is lacking. Glucocorticoid and opioid use is associated with possibly reversible reductions in circulating testosterone level, without elevation of LH and FSH levels. Where continuation of glucocorticoid or opioid therapy is necessary, review by an endocrinologist may be warranted. Changes in management as result of the position statement: Men with pathological hypogonadism should be identified and considered for testosterone therapy, while further research is needed to clarify whether there is a role for testosterone in these other settings.